Quality of life of the elderly residents of nursing homes and patients of the Psychogeriatric Day Ward - Pawlaczyk, Magdalena; Gąsior, Teresa; Michalak, Michał; Jóźwiak, Andrzej; Zasadzka, Ewa; Matecka, Monika; Pawlaczyk, Mariola (Journal of Medical Science, 2017)
Introduction. Due to the prolonged average life span and constantly increasing number of the elderly, research of this population’s quality of life (QoL) is being conducted to assess the spheres requiring improvement. Aim. To assess and compare the life quality in different domains between residents of nursing homes (NH) and patients of the Psychogeriatric Day Ward (PDW). Material and Methods. The study encompassed 68 PDW patients and 62 NH residents. The WHOQOL-BREF questionnaire and a structured interview concerning diseases, different forms of support and activities preferred were used. Results. Women predominated among the subjects (83%). The elderly aged 75–90 constituted the majority (64.62%). The average assessment of QoL in the whole group amounted to 3.6 points. No significant differences in the assessment of QoL satisfaction and one’s own health satisfaction were observed between PDW patients and NH residents. The participants of both groups assessed the highest QoL in the environment domain and the lowest in the social relationships domain. A relationship between higher QoL in the physical health domain and participation in social forms of spending free time was observed. Relationships between QoL in particular domains and age, marital status and length of stay in NH were found. Conclusions. Elderly people’s QoL, similarly to their satisfaction with health, were on an average level regardless of the institutional care. The QoL remains in a significant relationship with health. The changing needs of the elderly should be the basis for creating an individual plan of professional support.